Old Man's Playing Ground : Gaming and Trade on the Plains/Plateau Frontier - Yanicki, Gabriel M., 1978- (Book collections on Project MUSE., 2014)
Oral traditions of the Piikáni, together with textual records spanning centuries, reveal the enduring cultural significance of prehistoric intergroup trading and gaming grounds.